Fostering Students’ Creative Writing through Multimodal Strategies within a Linguistic Framework (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2025)
This study explores the implementation of multimodal strategies within a linguistic framework to enhance students’ creative writing skills. Conducted as a Classroom Action Research (CAR) at SMA Negeri 5 Palembang involving 30 Grade XI students, the research adopted a qualitative approach supported by descriptive quantitative data. The intervention was carried out in two cycles, incorporating visual, auditory, and interactive media to stimulate students’ imagination and linguistic expression. The information was gathered by observing and writing tests, interviewing and by document studies. The results indicated strong enhancement of students’ writing quality in all four language components tested (text structure, vocabulary, creativity, coherence). The mean writing score went up from 61.3 (pre-cycle) to 89 (post-test), particularly in creativity and vocabulary. Results also showed that multimodal techniques led to increased involvement, self-expression, and writing self-efficacy. Obstacles such as the lack of media literacy and technical barriers were overcome through scaffolding, group work, and the teachers' adaptation. The study argues that the incorporation of multimodal strategies in teaching creative writing leads to a dynamic, inclusive, and effectual teaching environment consistent with 21st century educational objectives.